2005
DOI: 10.28945/2927
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of National Culture on Worldwide eGovernment Readiness

Abstract: Diffusion of information and communication technologies is a global phenomenon. In spite of rapid globalization there are considerable differences between nations in terms of the adoption and usage of new technologies. Several studies exploring causal factors including national cultures of information and communication technology adoption have been carried out. The focus of this paper is slightly different from other studies in this area. Rather than concentrating on the individual information technology an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 17 publications
6
30
0
Order By: Relevance
“…In this regard, our study should contribute to the advancement of cross-cultural research as well as e-government diffusion. For example, our research findings could be used to correlate the effects of culture on e-government diffusion with research by others who have adopted A c c e p t e d M a n u s c r i p t 22 different cultural models [47,80]. Such research could lead to further theoretical development due to the convergent validity achieved by using various cultural models.…”
Section: Implications For Theoretical Developmentmentioning
confidence: 79%
See 3 more Smart Citations
“…In this regard, our study should contribute to the advancement of cross-cultural research as well as e-government diffusion. For example, our research findings could be used to correlate the effects of culture on e-government diffusion with research by others who have adopted A c c e p t e d M a n u s c r i p t 22 different cultural models [47,80]. Such research could lead to further theoretical development due to the convergent validity achieved by using various cultural models.…”
Section: Implications For Theoretical Developmentmentioning
confidence: 79%
“…The study of Akyut [7] showed a negative correlation between uncertainty avoidance and e-government adoption across the European countries studied. However, the results of statistical analysis of global data conducted by Kovačić [47] and Zhao [80] disputed this correlation. These inconsistent results warrant more empirical studies and testing.…”
Section: Uncertainty Avoidancementioning
confidence: 86%
See 2 more Smart Citations
“…In particular, researchers are trying to analyse the differences in the electronic development of states under the influence of the national-cultural factor by applying the Geert Hofstede model [15].…”
Section: Analysis Of Previous Studies and Statement Of The Problemmentioning
confidence: 99%